2012
DOI: 10.1002/srin.201200037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cold Forming and Heat Treatment on the Microstructure and Mechanical Properties of an Air‐Hardening Steel

Abstract: The use of air‐hardening steels in the manufacture of automobile body components shortens the corresponding process chain by means of eliminating the immersion or gas quenching operation since hardening occurs in still air. To choose the optimal forming and heat‐treatment parameters, the development of the microstructure needs to be considered as a consequence of the thermomechanical production processes. The object of this work is to investigate the effects of forming and the subsequent heat‐treating on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…Another approach to create a dual phase microstructure is the controlled cooling from austenitizing temperatures to room temperature by usage of, e.g., specified cooling rates or stepwise cooling. Here, the CCT diagram of this steel reveals the formation of a small amount of ferrite when cooling within 20 min from austenitizing temperatures to 700°C. This does not correspond to the here applied free air quenching conditions.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Another approach to create a dual phase microstructure is the controlled cooling from austenitizing temperatures to room temperature by usage of, e.g., specified cooling rates or stepwise cooling. Here, the CCT diagram of this steel reveals the formation of a small amount of ferrite when cooling within 20 min from austenitizing temperatures to 700°C. This does not correspond to the here applied free air quenching conditions.…”
Section: Discussionmentioning
confidence: 91%
“…The change of the microstructure and the properties due to cold plastic deformation and subsequent air-hardening, as well as the interaction between the yield stress and microstructural parameters were studied in. [8] The tensile strength, achieved by a combined treatment with optimal parameters exceeded 1000 MPa. Even higher strength values of about 1100 MPa were induced using press-hardening.…”
Section: Current State Of Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…In the above‐mentioned study, an influence of a relatively high tool temperature and a short austenitization on the properties of steel 22MnB5 were investigated. Nevertheless, as it has been reported by other researchers, lower temperature during austenitization is more preferable for achieving the finer prior austenite grain size and thus the improvement of mechanical properties …”
Section: Introductionmentioning
confidence: 79%
“…Nevertheless, as it has been reported by other researchers, lower temperature during austenitization is more preferable for achieving the finer prior austenite grain size and thus the improvement of mechanical properties. [15,18,19] In addition, previous studies demonstrated that the initial microstructure influences the a-g transformation and properties after cooling. Therefore, this influence should be also investigated for steel 22MnB5, which is available in a wide range of possible initial microstructures.…”
mentioning
confidence: 97%